Myrdal's Asian drama : an interdisciplinary critique - Maddison Angus (Belgium CIRIEC, 1971)
This paper attempts to understand Asian Drama in the context of the development debates of its time, and in terms of the sensibilities that Gunnar Myrdal-the brilliant economic theorist and philosopher of knowledge, and the Swedish politician-brought to the conceptualization of the problems and prospects of development. The paper covers: (i) what Gunnar Myrdal brought to the analysis of development from his long, varied and distinguished academic and practitioner career; (ii) the development terrain in the mid-twentieth century; and (iii) how Asian Drama lay on that terrain and in the remaining years of Gunnar Myrdal's continued eventful life. The two central questions posed in the paper are: (i) How did Gunnar Myrdal's broad experience and perspective influence Asian Drama? (ii) How did Asian Drama influence the development debate?
aia 01/02/2019
Loans
Keywords: Asian drama; Economic development - Asia; Living and inequality; Asia